Estetyka „zdrowego rozsądku”? - Budrewicz, Tadeusz; Okulicz-Kozaryn, Radosław (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2020)
The study discusses the polemic over the criteria and nature of realism in art. In 1885 Bolesław Prus criticized the means of determining values in art based on the categories of ideas because it defies common sense. Wiktor Gomulicki in turn, refuted the cognitive bases of realism. In this context, both sides advanced arguments for and against the concept of the ideal in art – taking as their palette of theories that of the aesthetic according to Hippolyte Taine and Eugène Véron. The brouhaha of 1885 saw a climax of polemics and the cut and thrust of opinions that concerned naturalism in literature, the historic in painting, painterly impressionism as well as that of monumental and allegoric art. The canvas upon which the war of words was waged concerned writers and painters grouped around the weekly Wędrowiec who campaigned for their manifesto, the polemic between Stanisław Witkiewicz and Henryk Struve on the meaning of colour and light in painting and the nation-wide discussion that ensued from the competition for a monument to the Polish bard Adam Mickiewicz. The most significant voices of polemic were published in the Warsaw press of the time and moreover, the echo of positions taken resounded throughout the breadth and width of Poland. Casting a glance as it were back to the polemic of 1885 affords one the opportunity to deepen and broaden discussion of what may be said to be a milestone in anti-positivist movements in the related arts of that period.
The Aesthetics of “Common Sense”?